Elisabeth Dupuy papers - Dupuy, Elisabeth, 1859-1932.
Chiefly manuscripts of Dupuy's poems, plays, and short stories. Also includes correspondence, notebooks, and other papers. Correspondents include Wilson Barrett, Beatrice Cameron Mansfield, and Richard Mansfield.
Author, poet, and playwright. Born Elizabeth Dupuy Smith.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Barrett, Wilson, -- 1848-1904 -- Correspondence; Mansfield, Beatrice Cameron, -- 1868- -- Correspondence; Mansfield, Richard, -- 1857-1907 -- Correspondence; American drama; American poetry; Short stories, American; Authors; Playwrights; Poets